2019
DOI: 10.1002/aoc.4871
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigation, DFT, fluorescence, molecular docking and biological studies of divalent and trivalent binuclear complexes prepared from benzoyl thiosemicarbazide derivative of 2‐benzylmalonohydrazide

Abstract: The binuclear Cr (III), Mn (II) and Fe (III) complexes of N,N′‐(2,2′‐(2‐benzylmalonyl)bis (hydrazine‐1‐carbonothioyl))dibenzamide (H4BPCD), which derived from the combination of 2‐benzylmalonohydrazide suspension with benzoyl‐isothiocyanate, have been isolated and investigated by the necessary analytical and spectroscopic techniques. The IR studies show that H4BPCD dispose as a mono‐negative hexadentate ligand (NOS)2 towards Mn (II) ion and tetra‐negative hexadentate (NOS)2 towards both Cr (III) and Fe (III) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Comparing the data of the ligand with the formed complexes, One can conclude the following remarks: As expected, all complexes except Cd(II) complex have bond angles similar to those expected for the octahedral complexes having sp 3 d 2 hybridization. [ 50,51 ] On the other hand, the optimized structure of Cd(II) complex seems to be tetrahedral. [ 48 ] (=C–O) enolic , (C=N) ring and (C=N) azomethine groups have longer bond lengths than those present in the parent ligand, resulting from the formation of M–N and M–O bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the data of the ligand with the formed complexes, One can conclude the following remarks: As expected, all complexes except Cd(II) complex have bond angles similar to those expected for the octahedral complexes having sp 3 d 2 hybridization. [ 50,51 ] On the other hand, the optimized structure of Cd(II) complex seems to be tetrahedral. [ 48 ] (=C–O) enolic , (C=N) ring and (C=N) azomethine groups have longer bond lengths than those present in the parent ligand, resulting from the formation of M–N and M–O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, all complexes except Cd(II) complex have bond angles similar to those expected for the octahedral complexes having sp 3 d 2 hybridization. [50,51] On the other hand, the optimized structure of Cd(II) complex seems to be tetrahedral. [48] ii.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…A vibration band occurring at 1612 cm −1 was credited to the stretching vibration of the C=N bond in the azomethine group of the L compound. However, this band shifted to lower wavenumbers in the chelate spectra around 1601 cm −1 ; this demonstrated the azomethine nitrogen involvement in the coordination [37][38][39][40][41]. The ν(Zr=O) in complex (4) was found as a medium band at 832 cm −1 [42].…”
Section: Ft-ir Spectra and Mode Of Bondingmentioning
confidence: 91%
“…Also, the activity against human tumor cells of hepatocellular carcinoma (HePG‐2) studies showed that the ligand has greater response than Cr (III) and Mn (II) complexes. [ 25 ] The chloro derivative, 2,2′‐malonylbis( N ‐(4‐chlorophenyl)hydrazine‐1‐carbothioamide), was utilized in electrochemical synthesis of binuclear metal complexes in anhydrous acetone solutions. The spectral studies revealed that the ligand acts in an SNO binegative tridentate fashion from each side through the enolic oxygen of the carbonyl group, the azomethine nitrogen and the thioenol of the thiocarbonyl group.…”
Section: Introductionmentioning
confidence: 99%